2017
DOI: 10.7196/sajbl.2017.v10i2.00610
|View full text |Cite
|
Sign up to set email alerts
|

How do healthcare professionals manage ethical challenges regarding information in healthcare professional/patient clinical interactions? A review of concept- or argument-based articles and case analyses

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…As Watts and Stenner ( 2005 , p. 74f) explain, Q-sort is mainly an exploratory methodology. The goal of this approach is to bring a sense of coherence to individual viewpoints or research questions that have many potentially complex and socially contested answers (Ewuoso et al, 2017 ; Roberts et al, 2015 Watts & Stenner, 2005 ;). Q-sort technique also has vertical and horizontal methodological usefulness.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As Watts and Stenner ( 2005 , p. 74f) explain, Q-sort is mainly an exploratory methodology. The goal of this approach is to bring a sense of coherence to individual viewpoints or research questions that have many potentially complex and socially contested answers (Ewuoso et al, 2017 ; Roberts et al, 2015 Watts & Stenner, 2005 ;). Q-sort technique also has vertical and horizontal methodological usefulness.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is not always clear how information should be managed within the clinical context. Information management here is understood as the power of health professionals to control the disclosure or withholding of information to their patients (Ewuoso et al, 2017 ). This encompasses information about diagnosis, prognosis, and preferred available therapy (Swaminath, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In different studies [4][5][6][7], I have shown that the above engagement is not only desirable, but possible. In one study Ewuoso [4], I showed how a particular African ethics may be used to address the ethical impasse created by applying coercion in psychiatric care.…”
Section: Opinionmentioning
confidence: 99%